RASIO PROFITABILITAS, LIKUIDITAS, LEVERAGE, FIRM SIZE, DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kartika Septiana, 10.05.52.0049; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2014)
Dividend policy is a guidelines set by the company to determine the amount of money that will paid as dividends to investors. The size of the dividends paid by the company to the investor depends on the dividend policy of each company. The purpose of this study is to examine and analyze the effect of pliers Profitability is measured by Return On Investment (ROI), Liquidity as measured by the current ratio (CR), Leverage as measured by Debt Equity Ratio (DER), Firm Size is measured by Ln Total Assets, and the Investment Opportunity Set measured by MVE / BVE.This study was conducted on 19 companies of the 134 listed companies in manufacturing companies in Indonesia Stock Exchange, which is selected through purposive sampling technique. Methods of analysis used in this study is multiple regression analysis.The results showed that: liquidity, leverage and investment opportunity set has a positive relationship to dividend policy. While the ratio of profitability and investment opportunity set has a negative relationship to the dividend policy.Keywords: Profitability, Liquidity, Leverage, Firm Size, Investment oppportunity Set, and Dividend Policy